2008
DOI: 10.4103/0970-4388.41622
|View full text |Cite
|
Sign up to set email alerts
|

Papillon-Lefevre syndrome: Report of two cases in the same family

Abstract: Papillon-Lefevre syndrome is a very rare syndrome of autosomal recessive inheritance characterized by palmar-plantar hyperkeratosis and early onset of a severe destructive periodontitis, leading to premature loss of both primary and permanent dentitions. Various etiopathogenic factors are associated with the syndrome but a recent report has suggested that the condition is linked to mutations of the cathepsin C gene. Two cases of Papillon-Lefevre syndrome in the same family, having all of the characteristic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…Chemotactic and phagocytic function of neutrophils is decreased in PLS, and it is associated with a diminished phytohemagglutinin response by T-cell lymphocytes [9, 12]. In consistence with previous reports, consanguineous marriage was found in fifty percent of our patients implying the genetic basis for the disease [14, 15]. Due to low socioeconomic status, genetic testing was not performed to identify responsible mutations.…”
Section: Discussionsupporting
confidence: 64%
“…Chemotactic and phagocytic function of neutrophils is decreased in PLS, and it is associated with a diminished phytohemagglutinin response by T-cell lymphocytes [9, 12]. In consistence with previous reports, consanguineous marriage was found in fifty percent of our patients implying the genetic basis for the disease [14, 15]. Due to low socioeconomic status, genetic testing was not performed to identify responsible mutations.…”
Section: Discussionsupporting
confidence: 64%
“…[1] Resorption of the alveolar bone gives the teeth a “floating-in-air” appearance on dental radiographs. [5]…”
Section: Introductionmentioning
confidence: 99%
“…The patient in this report had no structural deformities in her upper and lower extremities. [7][8][9][10][11][12][13] Psychosocial condition of a patient with PLS tends to be affected because of losing teeth at a young ages. Therefore, early dental evaluation is a significant step in psychological rehabilitation for children with PLS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Microbiological studies of plaque samples from patients with PLS have shown Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Fusobacterium nucleatum, and Treponema denticola organisms as examples of many pathogens that may be involved in this disease. 7 A. actinomycetemcomitans is most responsible in the pathogenesis of the rapid periodontal destruction in patients with PLS. 8 In addition to the dermatologic and oral findings, patients may have decreased neutrophil, lymphocyte, or monocyte functions and an increased susceptibility to bacterial infection, leading to persistent pyogenic infections of the skin.…”
mentioning
confidence: 99%